Grandmother's grandchild : my Crow Indian life - Snell, Alma Hogan (American Indian lives., 2000)
"Grandmother's Grandchild is the remarkable story of Alma Hogan Snell, a Crow woman brought up by her grandmother, the famous medicine woman Pretty Shield. Snell grew up during the 1920s and 1930s, part of the second generation of Crows to be born into reservation life. Like many of her contemporaries, she experienced poverty, personal hardships, and prejudice and left home to attend federal Indian schools." "What makes Snell's story particularly engaging is her exceptional storytelling style. She is frank and passionate, and these qualities yield a memoir unlike those of most Native women. The complex reservation world of Crow women - harsh yet joyous, impoverished yet rich in meaning - unfolds for readers. Snell's experiences range from the forging of an unforgettable bond between grandchild and grandmother to the flowering of an extraordinary love story that has lasted more than five decades."--Jacket